STUDENTS' SELF-REGULATED LEARNING STRATEGIES IN EFL : A Case Study in One of Senior High Schools in Bandung - Yulianti, Else (2015)
The study aimed to investigate students' self-regulated learning strategies in the three components, which were personal, behavioral, and environmental in learning English as foreign language. To gather data, questionnaire, interview, observation, and analysis of students' written notes were employed to a class of a public senior high school in Bandung, West Java. Then, the data that had been gathered were analyzed qualitatively. The findings indicated that the students demonstrated all personal, behavioral, and environmental self-regulated learning strategies in learning English in varying degrees. Most self-regulated learning strategies were frequently practiced by the students in learning English. Meanwhile, value encouragement (self-talk) strategy which was one of personal self-regulated learning strategies was found as the most frequently strategy used by the students. On the other hand, a strategy that was the least frequently demonstrated was self-consequating which belongs to behavioral self-regulated learning strategy. In addition, it was also found that the high and medium self-regulated learners were inclined to practice the self-regulated learning strategies in similar frequency of use and variety of strategies as they were aware of the importance of the strategies. In the other hand, although low self-regulated learners had been aware of the importance of the strategies, they were inconsistent in demonstrating those strategies. Considering the findings, it is suggested that the teacher should understand students' self-regulated learning strategies, promote and train self-regulated learning strategies which the students can practice in order to become self-regulated learners, also plan and organize classes in a way that facilitates the students to develop self-regulated learning. Keywords: self-regulated learning strategies, personal, behavioral, and environmental self-regulated learning strategies. Penelitan ini menyelidiki strategi self-regulated learning siswa dalam tiga komponen, yaitu personal, perilaku, dan lingkungan dalam belajar bahasa Inggris sebagai bahasa asing. Data dikumpulkan melalui kuisioner, interview, observasi, dan analisis buku catatan siswa yang dilakukan pada satu kelas sekolah menengah atas di Bandung. Data yang telah dikumpulkan lalu dianalisis secara kualitatif. Hasil menunjukkan bahwa siswa mempratekkan semua strategi self-regulated learning dalam belajar bahasa Inggris dengan berbagai tingkatan. Kebanyakan strategi self-regulated learning sering digunakan siswa. Sementara itu, value encouragement self-talk strategy yang merupakan salah satu dari strategi personal self-regulated learning adalah yang paling sering digunakan oleh siswa. Di sisi lain, strategi yang jarang digunakan adalah self-consequanting strategy yang merupakan salah satu dari strategi perilaku self-regulated learning. Selain itu, siswa dengan tingkat regulasi diri tinggi dan sedang cenderung menggunakan strategi dalam frekuensi dan variasi yang sama dimana mereka juga menyadari pentingnya penggunaan strategi-strategi tersebut. Sementara itu, meskipun siswa dengan tingkat regulasi diri rendah menyadari pentingnya penggunaan strategi-strategi self-regulated learning, mereka tidak konsisten dalam menggunakan strategi self-regulated learning. Berdasarkan hasil penelitian, disarankan pada guru untuk memahami strategi self-regulated learning siswa, mendukung serta melatih strategi-strategi tersebut agar siswa menjadi self-regulated learners. Selain itu, guru juga perlu untuk merancang kegiatan pembelajaran di kelas yang dapat memfasilitasi siswa untuk meningkatkan regulasi dirinya. Kata Kunci: strategi self-regulated learning, strategi personal, perilaku, dan lingkungan self-regulated learning.